2020
DOI: 10.1097/gme.0000000000001575
|View full text |Cite
|
Sign up to set email alerts
|

The effect of menopause on metabolic syndrome: cross-sectional results from the Canadian Longitudinal Study on Aging

Abstract: Objectives: Data were examined from women surveyed in the Canadian Longitudinal Study on Aging to evaluate whether menopause is an independent risk factor for the development of metabolic syndrome (MetS) or its components, including hypertension, central obesity, dyslipidemia, or elevated glycated hemoglobin. Methods: We conducted a cross-sectional analysis of women aged 45-85 years old that participated in the baseline data of the Canadian Longitudinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…Additionally, menopausal stage increased ORs of MetS, elevated blood pressure, and increased waist circumference in women living in high relative humidity compared to non-menopausal women living at the same humidity levels, indicating sex hormones may explain these differences. Several studies also revealed that menopause is associated with an increased risk of MetS and its components, which supports our outcomes [48][49][50].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, menopausal stage increased ORs of MetS, elevated blood pressure, and increased waist circumference in women living in high relative humidity compared to non-menopausal women living at the same humidity levels, indicating sex hormones may explain these differences. Several studies also revealed that menopause is associated with an increased risk of MetS and its components, which supports our outcomes [48][49][50].…”
Section: Discussionsupporting
confidence: 91%
“…28 In support of this hypothesis, it has been shown that surgically induced menopause increases the risk of developing insulin resistance and metabolic syndrome. 29 Clinical studies show that post-menopausal women are more susceptible than premenopausal women to develop dyslipidemia, an increase in body weight (evaluated through body mass index and waist circumference), and impaired glucose tolerance (as shown by their levels of hyperinsulinemia and increased fasting glucose levels). 28e31 Metabolic disturbances, such as insulin resistance, tend to dramatically increase with the onset of menopause, and estrogen replacement therapy significantly reduces the risk of metabolic syndrome.…”
Section: Overview Of Sex Differences In Insulin Resistancementioning
confidence: 99%
“…As a consequence of this trend, elderly women, both obese and non-obese, are at higher risk and therefore need to be more closely followed longitudinally. Appropriate interventions targeted at subjects with MetS may be an important preventive care to improve health and longevity, particularly in postmenopausal women [ 3 ].…”
Section: Introductionmentioning
confidence: 99%